Bibliometric analysis: global research trends in biogenic volatile organic compounds during 1991–2014 - Li, Yaqi; Jing Li; Shaodong Xie (Environmental Earth Sciences, 2017)
Bibliometric analysis was applied to identify global patterns and trends in the research of biogenic volatile organic compounds (BVOCs), which are important to atmospheric ozone formation and secondary organic aerosol formation. Yearly publications, mainstream subject categories and journals, leading countries and institutions, research emphases and trends were identified. Number of publications and times of citation were used as indicators to evaluate publication performances. A summary of the most frequently used keywords obtained from author keywords and KeyWords Plus provided clues for research emphases in different periods. A network of keywords was drawn to visualize the cross-relationship of keywords. Results indicated that annual output of the related scientific papers increased notably during 1991–2014. Atmospheric Sciences, Environmental Sciences & Ecology, Environmental Sciences & Engineering, and Chemistry were the main subject categories. Journal of Geophysical Research-Atmospheres was the most competitive journal in productivity and academic impact. The USA and the National Center for Atmospheric Research (NCAR) were, respectively, the leading country and leading institution in BVOC research. “Emissions,” “isoprene,” and “model” were the leading research emphases in BVOC field in terms of word frequencies and centrality driven from the network structure. The three leading research hotspots cross-fields, emissions-isoprene, emissions-model, and isoprene-model showed substantial growth in scientific outputs during the study period. These trends were evidenced by the evolution of research contents in various studies.